A rare cause of acute abdomen: acute cholecystitis secondary to polyarteritis nodosa - Zeki DÖŞEYEN; Aydın İNAN; Sancar BAYAR; Cihan BUMİN; Mahmut KESENCİ; Özden TOLUNAY (Turkish Journal of Gastroenterology, 2019)
-